Latitudinal- and height-dependent long-term climatology of propagating quasi-16-day waves in the troposphere and stratosphere - Wentao Tang; Shaodong Zhang; Chunming Huang; Kaiming Huang; Yun Gong; Quan Gan (Earth, Planets and Space, 2021)
Abstract The global amplitude of the westward propagating quasi-16-day waves (16DW) with wavenumber 1 (Q16W1), the strongest component of 16DW, are derived from the European Centre for Medium-Range Weather Forecasts ERA-Interim reanalysis temperature and zonal wind data sets from February 1979 to January 2018. In terms of temperature and zonal wind, strong climatologically average amplitudes of Q16W1 appear in the upper stratosphere at mid–high latitudes in both hemispheres, and the wave amplitude is stronger in the Northern Hemisphere (NH) than in the Southern Hemisphere (SH). Multivariate linear regression is separately applied to calculate the responses of the Q16W1 temperature and zonal wind amplitudes to the QBO (quasi-biennial oscillation), ENSO (El Niño-Southern Oscillation), solar activity and linear trends of the Q16W1 amplitude. The QBO signatures of the Q16W1 temperature and zonal wind amplitudes are mainly located in the stratosphere. The Q16W1 has significant QBO responses at low latitudes. In addition, only the temperature amplitude presents a larger QBO signature in its strongest climatological amplitude region. No significant responses to ENSO and solar activity are observed in temperature and zonal wind amplitudes. The linear trends of the monthly mean Q16W1 temperature and zonal wind amplitude are generally positive, especially in the mid-upper stratosphere. The trend is asymmetric about the equator and significantly stronger in the NH than in the SH. The seasonal variation in the trend of the temperature amplitude is studied and illustrated to be stronger in winter and weaker in spring and autumn. Further investigation suggests that the background and local instability trends contribute most of the increasing trend of the Q16W1 amplitude. In winter in both hemispheres, a weakening trend of eastward zonal wind provides more favourable background wind for Q16W1 upward propagation, in autumn and winter in the NH and in spring, autumn and winter in the SH, and the increasing trend of local instability may enhance wave excitation. Graphical Abstract